An assessment of the Western Nigeria Legislature and Infrastructure Development, 1952 – 1965 - O. Akobi, Benjamin (Kashere Journal of Humanities, Management and Social Sciences, 2022)
This study interrogates the nexus between legislative practice and infrastructure development in the Western Region of pre – independence Nigeria up to the First Republic. The post-Second World War constitutional reforms introduced by the colonial government in Nigeria granted the political elites increased power to influence the socio-economic transformation of their regions. In the light of this, the regional parliaments passed various legislative Acts for the purpose of development, of which provision of infrastructures formed a significant core. It is widely acknowledged that in terms of socio-economic development, of all the component units of the Nigeria Federation, the Western Region of Nigeria during the period under study was a primus inter pares. However, the manner and tempo of how legislative powers were employed to facilitate infrastructure development, the degree and spread of such development, and the constraints encountered in the process are worthy of discussion. This paper discusses these phenomena in the context of developments in the Western Region from a historical perspective, using qualitative method.